Digitalisierung als Herausforderung für Personalentwicklung und Mitbestimmung Unternehmensstrategien der IT-Branche und ihre Bedeutung für Weiterbildung - Langemeyer, Ines (Verlag Barbara Budrich, 2018)
The ability to innovate is a valuable asset for the IT industry. Special knowledge, farsightedness, problem-solving skills, productive collaboration and the willingness to think and act independently play a major role. In particular, the study examines small and medium-sized enterprises, the special focus they have on vocational learning and how they approach questions of continuing training in practice.